Optimising the Performance of Cement-Based Batteries. (20th August 2017) - Byrne, Aimee; Barry, Shane; Holmes, Niall; Norton, Brian
Abstract : The development of a battery using different cement-based electrolytes to provide a low but potentially sustainable source of electricity is described. The current, voltage, and lifespan of batteries produced using different electrolyte additives, copper plate cathodes, and (usually) aluminium plate anodes were compared to identify the optimum design, components, and proportions to increase power output and longevity. Parameters examined include water/cement ratio, anode to cathode surface area ratio, electrode material, electrode spacing, and the effect of sand, aggregate, salts, carbon black, silica fume, and sodium silicate on the electrolyte. The results indicate that the greatest and longest lasting power can be achieved using high proportions of water, carbon black, plasticiser, salts, and silica fume in the electrolyte and using a magnesium anode and copper cathode. This cell produced an open-circuit voltage of 1.55 V, a resistor-loaded peak current over 4 mA, maintaining over 1 mA for 4 days, and a quasi steady current of 0.59 mA with a lifespan of over 21 days.